A Comparison Between Chemo-Radiotherapy Combined With Immunotherapy and Chemo-Radiotherapy Alone for the Treatment of Newly Diagnosed Glioblastoma: A Systematic Review and Meta-Analysis - Lara-Velazquez, Montserrat; Shireman, Jack M.; Lehrer, Eric J.; Bowman, Kelsey M.; Ruiz-Garcia, Henry; Paukner, Mitchell J.; Chappell, Richard J.; Dey, Mahua (Frontiers in Oncology, 2021)
Background Immunotherapy for GBM is an emerging field which is increasingly being investigated in combination with standard of care treatment options with variable reported success rates. Objective To perform a systematic review of the available data to evaluate the safety and efficacy of combining immunotherapy with standard of care chemo-radiotherapy following surgical resection for the treatment of newly diagnosed GBM. Methods A literature search was performed for published clinical trials evaluating immunotherapy for GBM from January 1, 2000, to October 1, 2020, in PubMed and Cochrane using PICOS/PRISMA/MOOSE guidelines. Only clinical trials with two arms (combined therapy vs. control therapy) were included. Outcomes were then pooled using weighted random effects model for meta-analysis and compared using the Wald-type test. Primary outcomes included 1-year overall survival (OS) and progression-free survival (PFS), secondary outcomes included severe adverse events (SAE) grade 3 or higher. Results Nine randomized phase II and/or III clinical trials were included in the analysis, totaling 1,239 patients. The meta-analysis revealed no statistically significant differences in group’s 1-year OS [80.6% (95% CI: 68.6%–90.2%) vs. 72.6% (95% CI: 65.7%–78.9%), p = 0.15] or in 1-year PFS [37% (95% CI: 26.4%–48.2%) vs. 30.4% (95% CI: 25.4%–35.6%) p = 0.17] when the immunotherapy in combination with the standard of care group (combined therapy) was compared to the standard of care group alone (control). Severe adverse events grade 3 to 5 were more common in the immunotherapy and standard of care group than in the standard of care group (47.3%, 95% CI: 20.8–74.6%, vs 43.8%, 95% CI: 8.7–83.1, p = 0.81), but this effect also failed to reach statistical significance. Conclusion Our results suggests that immunotherapy can be safely combined with standard of care chemo-radiotherapy without significant increase in grade 3 to 5 SAE; however, there is no statistically significant increase in overall survival or progression free survival with the combination therapy.